Cyanobacterial harmful algal blooms : state of the science and research needs - Hudnell, H. Kenneth (Advances in experimental medicine and biology, 2008)
Cyanobacteria are single-celled organisms that live in fresh, brackish, and marine water. They use sunlight to make their own food. In warm, nutrient-rich environments, microscopic cyanobacteria can grow quickly, creating blooms that spread across the water??'s surface and may become visible. Because of the color, texture, and location of these blooms, the common name for cyanobacteria is blue-green algae. However, cyanobacteria are related more closely to bacteria than to algae. Cyanobacteria are found worldwide, from Brazil to China, Australia to the United States. In warmer climates, these.